ENGLISH AS THE LANGUAGE OF SCIENCE: THE ROLE OF ENGLISH IN THE ACADEMIC WORLD - Selvi, Batuhan (My University, 2021)
English has been used as the primary language of academic publications andinternational research. Many academic institutions worldwide have founded theirhiring, promotion, reward and graduation systems on publishing in internationalindexed journals. In this sense, academic members and graduate students have nochoice but to publish in international arena which is tremendously dominated byEnglish. The aim of this paper is to investigate the role English played in theacademic world. As a part of this paper, first the position of English will beexamined from a historical perspective and then the current position of English inthe academic world will be described. Further, a brief literature analysis withregard to the international scholars’ problems in writing for academic publicationprocess and the strategies they use to deal with these problems will be provided.Finally, the role English play in Turkish academia will be discussed. It is concludedin this paper that although international scholars have a number of difficulties, theyalso have a number of strategies to overcome the problems in writing for scholarlypublication.
Keywords: Eğitim; Eğitim Araştırmaları; Dil ve Dil Bilim